No vai e vem das marés, o movimento da vida: mulheres, família e trabalho na Ilha de Quianduba, Abaetetuba/PA - AMARAL, Waldileia Rendeiro da Silva (Universidade Federal do Pará, 2017)
This study presents the dynamic and the cultural variability of families that belong to a social segment from Amazonia historically called ribeirinho (not always named like that by themselves) who live in an area close to Abaetetuba Islands. From the relationship between family and work - including gender's injunctions focused on female leadership inside the current dynamic family's organization - I aim to understand how the families' reconfiguration happens, considering their profiles, relatives groups (even though variable) and important aspects that build the familiar environment. I observe carefully the functions of men and women (including children), their ways of bringing material and affective provisions, the using of money, the domestic work and production. These study objects are seeimg considering the gender relations and its influence during family routine (generating and steps of the circle of life), especially the meaning of the life that they live.